Stochastic frontier approach for measuring online bank efficiency in the Kuala Lumpur Stock Exchange market - Baten, Md Azizul; Mat Kasim, Maznah; Ramli, Razamin; Mohd Jamil, Jastini (ARRAY Development, 2014)
Bank Efficiency is important and receives greater attention as it plays an essential role in the economic development. This study formulated an appropriate stochastic frontier model to investigate the efficiency of banks traded on Kuala Lumpur Stock Exchange (KLSE) market during the period 2005-2009. All data were analyzed using the maximum likelihood method to estimate the parameters of stochastic frontier production model. Unlike the earlier studies which use balance sheet and income statements data, this study used market data as the input and output variables. It was observed that banks traded in KLSE exhibited a commendable overall efficiency level of 96.2% during 2005- 2009 hence suggesting minimal input waste of 3.8%. The technical efficiency effects were observed increasing over time. Among the banks, the COMS (Cimb Group Holdings) bank was found to be highly efficient with a score of 0.9715 and BIMB (Bimb Holdings) bank was noted to have the lowest efficiency with a score of 0.9582. The results also showed that Cobb-Douglas stochastic frontier model with truncated normal distributional assumption was found preferable than Translog stochastic frontier model.